A biomass waste evaluation for power energy generation in Mexico based on a SWOT & Fuzzy-logic analysis - Hernandez-Escalante, Mariana; Martin-del-Campo, Cecilia (International Journal of Sustainable Energy Planning and Management, 2022)
Power energy generation in Mexico based on bioenergy is currently insignificant. However, the potential for taking advantage of biomass resources in the country is considerable. This article aims to evaluate the use of biomass waste for the Mexican energy transition in the near future. The methodology starts by identifying sites with biomass waste and establishing the conversion processes needed to produce electricity for each type of biomass. A SWOT analysis was implemented to define the criteria for evaluating all options on the same basis. The opinion of experts in energy systems was collected to assign the priority to each criterion. A fuzzy-logic inference system was formulated to assess the options based on the quality of their attributes. The output obtained from the fuzzy analysis is a sustainability prioritisation of all options. We analysed a case study for the Baja California Sur (BCS) region, and the results show the prioritisation ranking of 24 alternatives regarding the sustainable use of bioenergy in the region and we made a proposal of an indicative plan to introduce bioenergy in the region from now until 2032. If the indicative plan were implemented, 61% of the power demand of BCS could be covered with bioenergy by 2032.